Sarcopenia, physical frailty, undernutrition and obesity cooccurrence among Portuguese community-dwelling older adults: results from Nutrition UP 65 cross-sectional study - Sousa-Santos, AR (2020)
Objectives. To investigate the coexistence of sarcopenia, frailty, undernutrition and obesity and to identify the factors associated with the cooccurrence of these conditions in an older population. Design. Cross-sectional. Setting. Portugal. Participants. 1454 older adults with 65 years or older, from Nutrition UP 65 study. Primary and secondary outcome measures. Sarcopenia was identified using the European Working Group on Sarcopenia in Older People 2 guidelines and physical frailty using Fried phenotype. Mini-Nutritional Assessment-Short Form was used to ascertain undernutrition, and obesity was evaluated by body mass index. Results. 57.3% presented at least one condition, 38.0% were identified with one and 19.3% were identified with two or more conditions. When all preconditions were considered, 95.7% of the older adults presented at least one of these preconditions or conditions. Multinomial logistic regression multivariate analysis revealed that being male (OR 0.61; 95% CI 0.43 to 0.88), being married or in a common-law marriage (OR 0.58; 95% CI 0.40 to 0.84) and having a higher educational level (OR 0.23; 95% CI 0.07 to 0.73) were inversely associated with having two or more conditions, while age >75 years (OR 1.60; 95% CI 1.14 to 2.24), a poor self-perception of health status (OR 5.61; 95% CI 3.50 to 9.01), ≥5 medications (OR 3.11; 95% CI 1.77 to 5.46) and cognitive impairment (OR 1.84; 95% CI 1.37 to 2.48) were directly associated. Conclusions. Almost three out of five older adults presented at least one of the conditions related to nutritional status, and about one in five had two or more of these occurrences. However, the low coexistence observed between all of these reinforces the need to assess them all individually during the geriatric assessment.